Mathematical approach for better mine waste rock dumping management - Li, Y.; Topal, Erkan; Williams, D. (Australasian Institute of Mining and Metallurgy, 2012)
A mine waste rock dump does not have any intrinsic value, yet is an inevitable structure in surface mining operations. Since the purpose of mining is to maximise profit, possible expenditure reduction in hauling waste rock to the dump, which can represent up to 50% of the total operating cost, is highly desirable. Apart from cost, potential acid mine drainage (AMD), due to seepage from surface waste rock dumps containing reactive waste rock, could threaten the ecological balance, drinking water supplies and irrigation systems downstream from a mine site. In order to minimise these potential risks, selective placement of benign and reactive waste rock, and the encapsulation of reactive waste rock by benign rock, need to be carried out during the construction of the dump. In this paper, a new methodology, based on mixed integer programming (MIP) is developed to manage waste rock dumping. The model aims to minimise waste rock haulage costs by locating the optimum destination(s) for each waste block, while at the same time controlling the placement of reactive waste rock to minimise the potential for AMD. Tests on small-scale virtual data demonstrated that the model is capable of dealing with selective placement of different waste rock types, encapsulating reactive, potentially acid forming (PAF) waste rock, and stockpiling benign waste rock for encapsulation and rehabilitation purposes. The solution time for the MIP model is far less than the traditional manual approach, and the resulting schedule is up to 30% more cost-effective.